Research and determination of process parameters of milk lactose hydrolysis - Калинина, Елена Дмитриевна; Коваленко, Александр Владимирович (Eastern-European Journal of Enterprise Technologies, 2014)
The researches of enzymatic milk lactose hydrolysis by using the β - galactosidase enzyme are given in the paper. For carrying out a lactose hydrolysis, two β-galactosidase enzyme preparations GODO-YNL2 and Neolactase are offered. For setting lactose hydrolysis parameters, the influence of a pH medium, temperature, enzyme preparation doses, the duration of hydrolyzing the milk lactose affected by the β- galactosidase enzyme preparations, was studied. In terms of effectiveness, adaptability and efficiency for the lactose hydrolysis, the GODO-YNL2 enzyme preparation was chosen. It was found that depending on the degree of lactose hydrolysis the milk sweetness increases, organoleptic indicators of hydrolyzed milk were defined, the milk sweetness index at different degrees of lactose hydrolysis was set, titratable and active acidity indicators of hydrolyzed milk were determined. The technological regimes of hydrolyzing lactose by enzymes were developed and substantiated: the temperature is 4-6 .C, the enzyme preparation dose is 0.01 and 0.02 %, the duration is 18-20 and 13-15 hours; the temperature is 43-45 .C, the enzyme preparation dose is 0.03 %, the duration is 3.5- 4 hours. For inactivating the enzyme, and producing high-quality sweet condensed milk, it was suggested carrying out milk pasteurization, after hydrolyzing lactose. In the subsequent work, it is proposed to use hydrolyzed skimmed and whole milk for manufacturing preserved sweet milk products.